2010
DOI: 10.1200/jco.2010.28.18_suppl.lba1010
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib (SU) in combination with docetaxel (D) versus D alone for the first-line treatment of advanced breast cancer (ABC).

Abstract: LBA1010 Background: Taxane-based chemotherapy (CT) improves progression-free survival (PFS) in patients (pts) with newly diagnosed HER2-negative metastatic BC (MBC). SU, an oral multitargeted tyrosine kinase inhibitor (MTKI), demonstrated antitumor activity in combination with D in a phase I/II study in pts with MBC. A randomized, open-label, multicenter phase III trial in pts with newly diagnosed ABC tested the hypothesis that addition of a MTKI to D improves PFS vs. D alone. Methods: Eligible pts (female; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 0 publications
1
25
0
3
Order By: Relevance
“…Two further phase III trials of sunitinib in patients with metastatic breast cancer were presented at ASCO 2010. In a first-line study, the addition of sunitinib to docetaxel significantly improved response rate (51% compared with 39%), but did not improve PFS, the primary endpoint of the study (hazard ratio 0.92; median 8.6 vs. 8.3 months) [21]. In the setting of second-line therapy or beyond, the addition of sunitinib to capecitabine did not improve PFS or response rate [22].…”
Section: Discussionmentioning
confidence: 97%
“…Two further phase III trials of sunitinib in patients with metastatic breast cancer were presented at ASCO 2010. In a first-line study, the addition of sunitinib to docetaxel significantly improved response rate (51% compared with 39%), but did not improve PFS, the primary endpoint of the study (hazard ratio 0.92; median 8.6 vs. 8.3 months) [21]. In the setting of second-line therapy or beyond, the addition of sunitinib to capecitabine did not improve PFS or response rate [22].…”
Section: Discussionmentioning
confidence: 97%
“…& Tyrosine kinase inhibitors targeting angiogenesis have also been clinically investigated. One such inhibitor, sunitinib, has been evaluated alone or in combination with chemotherapy but the results have been disappointing [69][70][71]. Subset analyses of patients with triple-negative disease in these studies suggested a benefit and led to trials of sunitinib in combination with chemotherapy in the neoadjuvant setting [72].…”
Section: Antiangiogenic Agentsmentioning
confidence: 99%
“…Durch Sunitinib konnte keine statistisch signifikante Verbesserung des progressionsfreien Überle-bens (PFS, primärer Endpunkt) nachgewiesen werden [51]. Ähnliche Ergebnisse zeigte auch eine Phase-III-Studie mit Docetaxel und Sunitinib vs. Docetaxel in der First-line-Behandlung des fortgeschrittenen Mammakarzinoms [52].…”
Section: Angiogeneseinhibitionunclassified